Active Conservation of Noncoding Sequences Revealed by Three-Way Species Comparisons - Dubchak, Inna; Brudno, Michael; Loots, Gabriela G.; Pachter, Lior; Mayor, Chris; Rubin, Edward M.; Frazer, Kelly A.

(untitled) (Genome Research, 2000)
Human and mouse genomic sequence comparisons are being increasingly used to search for evolutionarily conserved gene regulatory elements. Large-scale human–mouse DNA comparison studies have discovered numerous conserved noncoding sequences of which only a fraction has been functionally investigated A question therefore remains as to whether most of these noncoding sequences are conserved because of functional constraints or are the result of a lack of divergence time.[The sequence data described in this paper have been submitted to the GenBank data library under accession nos. AF276990.]